102-2008&2009-1-M20-Dec2008

102-2008&2009-1-M20-Dec2008 - 2 sec 2 θ dθ = Z 1 +...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
Kuwait University Math 102 December 14, 2008 Second Midterm Duration: 90 minutes Calculators and mobile phones are not allowed. Answer all of the following questions. 1. Evaluate the following limits. (2 points each) (a) lim x 0 cos7 x - cos3 x 2 x 2 (b) lim x 0 + (1 + sin3 x ) 1 tan - 1 (2 x ) 2. Evaluate the following integrals. (3.5 points each) (a) Z x 3 + 4 x x 2 - 4 dx (b) Z sin 5 2 x sec 3 x dx (c) Z x 2 2 x dx (d) Z x ( x 2 - 4 x + 8) 3 2 dx (e) Z x 1 2 - 1 x ( x 1 6 + x 1 2 ) dx (f) Z tanh 5 x sech xdx
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Solutions 1. (a) lim x 0 cos7 x - cos3 x 2 x 2 L 0 H = lim x 0 - 7sin 7 x + 3sin 3 x 4 x L 0 H = lim x 0 - 49cos 7 x + 9 cos3 x 4 = - 10 (b) lim x 0 + ln(1 + sin3 x ) tan - 1 (2 x ) L 0 H = lim x 0 + 3cos3 x 1+sin3 x 2 1+4 x 2 = 3 2 therefore lim x 0 + (1 + sin 3 x ) 1 tan - 1 (2 x ) = e 3 2 2. (a) Z x 3 + 4 x x 2 - 4 dx = Z ± x + 8 x ( x - 2)( x + 2) dx = x 2 2 + Z ± 4 x - 2 + 4 x + 2 dx = x 2 2 + 4(ln | x - 2 | + ln | x + 2 | ) + C (b) Let u = sin x . Then Z sin 5 2 x cos 3 xdx = Z u 5 2 (1 - u 2 ) du = Z u 5 2 - u 9 2 · du = 2 7 sin 7 2 x - 2 11 sin 11 2 x + C (c) We use integration by parts twice with dv = 2 x dx : Z x 2 2 x dx = x 2 2 x ln2 - 2 ln2 Z x 2 x dx = x 2 2 x ln2 - 2 ln2 ± x 2 x ln2 - 1 ln2 Z 2 x dx = x 2 2 x ln2 - 2 ln2 ± x 2 x ln2 - 2 x (ln2) 2 + C (d) I = Z xdx ( x 2 - 4 x + 8) 3 2 = Z xdx (( x - 2) 2 + 4) 3 2 . Let x - 2 = 2tan θ . Then I = Z 2 + 2 tan θ 8sec 3 θ
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 2 sec 2 θ dθ = Z 1 + tan θ 2sec θ dθ = 1 2 Z (cos θ + sin θ ) dθ = 1 2 (sin θ-cos θ ) + C = 1 2 ± x-2 √ x 2-4 x + 8-2 √ x 2-4 x + 8 ¶ + C = x-4 2 √ x 2-4 x + 8 + C (e) Let x = u 6 . Then Z x 1 2-1 x ( x 1 6 + x 1 2 ) dx = Z u 3-1 u 6 ( u + u 3 ) 6 u 5 du = 6 Z u 3-1 u 2 (1 + u 2 ) du = 6 Z ±-1 u 2 + u + 1 1 + u 2 ¶ du = 6 ± 1 u + 1 2 ln ( 1 + u 2 ) + tan-1 u ¶ + C = 6 6 √ x + 3ln ( 1 + 3 √ x ) + 6 tan-1 6 √ x + C (f) I = Z tanh 5 x sech xdx = Z ( 1-sech 2 x ) 2 tanh x sech xdx. Let u = sech x . Then I =-Z ( 1-u 2 ) 2 du =-Z ( 1-2 u 2 + u 4 ) du =-sech x + 2 3 sech 3 x-1 5 sech 5 x + C...
View Full Document

This note was uploaded on 02/23/2010 for the course CAL B 0410102 taught by Professor Deparpment during the Spring '10 term at Kuwait University.

Page1 / 2

102-2008&2009-1-M20-Dec2008 - 2 sec 2 θ dθ = Z 1 +...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online